Diesel-Biodiesel Blend on Engine Performance: An Experimental Study - Agus Choirul Arifin; Achmad Aminudin; Roby Mahendra Putra (Automotive Experiences, 2019)
This article discusses engine performance using diesel oil and biodiesel obtained from the reaction of vegetable oils with alcohol through the process of alcoholysis. Tests carried out on variations of diesel oil 100% (B0), 10% biodiesel (B10), 20% biodiesel (B20) and 30% biodiesel (B30). Engine performance testing is carried out at 1500 rpm to 4000 rpm at intervals of 500 rpm. The highest torque is obtained at 2000 rpm using B0, B10 and B20 of 310.3 Nm, 306 Nm and 308.1 Nm, respectively. The highest power is obtained at 3000 rpm using B0, B10 and B20 of 114.7 hp, 115.1 hp and 114.9 hp, respectively. The average fuel consumption with B0, B10 and B20 is 1.42 ml/s, 1.54 m/s, and 1.74 ml/s, respectively. B30 fuel cannot be tested on a vehicle due to detonation so that combustion does not occur completely and B30 fuel properties are incompatible with the vehicle being tested.